2022
DOI: 10.1002/jctb.7131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of biofilm carriers of varying shapes, sizes, and materials for wastewater treatment in fixed bed biofilm reactor: a qualitative study of biocarrier performance

Abstract: BACKGROUND Biofilm carriers were introduced in the early 1990s mainly to abate chemical oxygen demand (COD). However, studies have continued investigating few biocarriers repeatedly, without studying a large number of carriers in a single study under similar conditions. RESULTS The current study investigated the performance of nine synthetic and eight natural biofilm carriers for 7 days of palm oil mill effluent (POME) treatment in terms of COD removal. A fixed bed biofilm reactor (FBBR) was 100% packed with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that the research of Chioti et al (2022) [15], who studied the efficiency of Kaldnes K1 commercial biocarriers and 3Dprinted biocarriers with 13X and bentonite in aerobic wastewater treatment performed in lab reactors of 150 mL active volume, has also shown a remarkable efficiency in wastewater treatment. According to other researchers [16], the synthetic biofilm carriers showed unstable COD removal rates, in contrast to the natural biofilm carriers that did not present any instability. This is due to the surface properties of the natural biofilm carriers, such as surface pores and roughness.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is worth mentioning that the research of Chioti et al (2022) [15], who studied the efficiency of Kaldnes K1 commercial biocarriers and 3Dprinted biocarriers with 13X and bentonite in aerobic wastewater treatment performed in lab reactors of 150 mL active volume, has also shown a remarkable efficiency in wastewater treatment. According to other researchers [16], the synthetic biofilm carriers showed unstable COD removal rates, in contrast to the natural biofilm carriers that did not present any instability. This is due to the surface properties of the natural biofilm carriers, such as surface pores and roughness.…”
Section: Introductionmentioning
confidence: 84%
“…Based on Figure 3 and on the influent/affluent COD values, it can be concluded that there is an excellent effluent quality in all three cases, with a removal rate of 88% for the control MBBR, 92% for MBBR K1 (slightly increased) and of 84% for MBBR 3D (slightly decreased). Other researchers [16] have concluded that COD removal when using synthetic biocarriers (including Kaldnes K1 biocarriers) in smaller-scale experiments is unstable. However, this was not found in the large-scale experiments of this research, as the COD removal was increasing steadily during the operating time of the unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the research of Chioti et al (2022) [16], who studied the efficiency of Kaldnes K1 commercial biocarriers and 3D-printed biocarriers with 13X and bentonite in aerobic wastewater treatment performed in lab reactors of 150 mL active volume, has also shown remarkable efficiency in wastewater treatment. According to other researchers [17], the synthetic biofilm carriers showed unstable COD removal rates, in contrast to the natural biofilm carriers that did not present any instability. This is due to the surface properties of the natural biofilm carriers, such as surface pores and roughness.…”
Section: Introductionmentioning
confidence: 84%
“…The main functions of the sand particles in BSRs are to trap solids and provide large surface areas and robust biofilm attachment sites for the microbial communities responsible for biodegradation of pollutants in WW [15]. It has been shown that the extensive rough surfaces of sand grains promote biofilm growth more effectively than synthetic biofilm attachment alternatives [15]. In BSRs, contact between the microbial communities and the pollutants takes place as the WW passively permeates through the interpore spaces in the sand [16].…”
Section: Introductionmentioning
confidence: 99%